STRATEGI GURU PAI DALAM MENGATASI KESULITAN BELAJAR SISWA PADA PENDIDIKAN AGAMA ISLAM - Syakila Hasanah Putri; Ilham Fahmi; Fatimah Az-Zahro (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Challenges faced by students in studying Islamic religious education. Related to procedures, content limitations, and student challenges related to material covering verses of the Qur'an, as well as reading and writing the Qur'an, especially those related to ability. Please note. After that, an assessment was conducted using Islamic Religious Education Teacher Strategies to help students who experience learning difficulties, including interacting directly with students, providing understanding and guidance on religious knowledge through various methods, and providing guidance through the Tahfis and Rohi programs three times a week. The low reading and writing abilities of students at the early education level, coupled with a lack of interest and enthusiasm for learning are examples of internal variables. Teacher factors can be examples of external factors. These include teaching strategies and media that are not appropriate to student characteristics and household elements that neglect their children. Student motivation to learn can decrease due to additional variables, such as cell phone use.